The Lure of Authoritarianism : The Maghreb after the Arab Spring - Moulay Hicham, Prince of Morocco, 1964-; Maghraoui, Abdeslam; King, Stephen J., 1961- (Book collections on Project MUSE., 2019)
The works collected in The Lure of Authoritarianism consider the normative appeal of authoritarianism in light of the 2011 popular uprisings in the Middle East. Despite what seemed to be a popular revolution in favor of more democratic politics, there has instead been a slide back toward authoritarian regimes that merely gesture toward notions of democracy. In the chaos that followed the Arab Spring, societies were lured by the prospect of strong leaders with firm guiding hands. The shift toward normalizing these regimes seems sudden, but the works collected in this volume document a gradual shift toward support for authoritarianism over democracy that stretches back decades in North Africa. Contributors consider the ideological, socioeconomic, and security-based justifications of authoritarianism as well as the surprising and vigorous reestablishment of authoritarianism in these regions. With careful attention to local variations and differences in political strategies, the volume provides a nuanced and sweeping consideration of the changes in the Middle East in the past and what they mean for the future